A Silent Corticotroph Pituitary Carcinoma: Lessons From an Exceptional Case Report - Remón-Ruiz, Pablo; Venegas-Moreno, Eva; Dios-Fuentes, Elena; Moreno, Juan Manuel Canelo; Fernandez Peña, Ignacio; Garcia, Miriam Alonso; Japón-Rodriguez, Miguel Angel; Roldán, Florinda; Fajardo, Elena; Kaen, Ariel; Ruiz-Valdepeñas, Eugenio Cardenas; Cano, David; et al. (Frontiers in Endocrinology, 2021)
Nowadays, neither image nor pathology evaluation can accurately predict aggressiveness or treatment resistance of pituitary tumors at diagnosis. However, histological examination can provide useful information that might alert clinicians about the nature of pituitary tumors. Here, we describe our experience with a silent corticothoph tumor with unusual pathology, aggressive local invasion and metastatic dissemination during follow up. We present a 61-year-old man with third cranial nerve palsy at presentation due to invasive pituitary tumor. Subtotal surgical approach was performed with a diagnosis of silent corticotroph tumor but with unusual histological features (nuclear atypia, frequent multinucleation and mitotic figures, and Ki-67 labeling index up to 70%). After a rapid regrowth, a second surgical intervention achieved successful debulking. Temozolomide followed by stereotactic fractionated radiotherapy associated with temozolomide successfully managed primary tumor however, sacral metastasis showed up 6 months after radiotherapy treatment. Due to aggressive distant behavior, carboplatine-etoposide scheme was decided but patient died of urinary sepsis 31 months after the first symptoms. Our case report shows how the presentation of a pituitary tumor with aggressive features should raise a suspicion of malignancy and the need of follow up by multidisciplinary team with experience in their management. Metastases may occur even if the primary tumor is well controlled..